Asuhan Kebidanan Berkelanjutan Pada Ny. Sm, Ny. Sk, Ny. S di PMB Dewi Rianasari, S.Tr.Keb - Dewi Rianasari; Yona Desni Sagita; Inggit Primadevi (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Pregnancy, childbirth, childbirth, newborns and family planning (KB) are physiological conditions, but you must be careful if conditions occur that can threaten the life of the mother or fetus. This can be prevented by providing good services during pregnancy, childbirth, postpartum, newborns and family planning. The aim of this report is to improve the quality of services with continuous contact between patients and health workers, including monitoring the condition of pregnant women from the beginning of pregnancy to the delivery process, monitoring BBL for signs of infection, postnatal complications and facilitating for couples of childbearing age in the service. KB. In this report, the approach used is in the form of a case study, where the author collects data and describes the process of comprehensive midwifery care based on Continue Of Care for TM III pregnant women, maternity, postpartum, BBL, and family planning using the SOAP approach. The results of the report showed that there were no gaps in pregnancy, childbirth, postpartum period, BBL and family planning. With continuous monitoring of Mrs. SM, Mrs. SK and Mrs. S. The condition of the mother and baby was monitored well without any accompanying complications.